Beauty Representation in Skin Game’s Instagram Post #BornThisWay - Wargi, Nabila Cahyaning (Kirana Publisher (KNPub), 2024)
Beauty is something that is considered quite important to have and is every woman's dream. Even though each individual's standard of beauty is different, there is a kind of unwritten standard that is embedded in people's minds regarding what beauty is. Over time and the development of technology, the dominance of the media, beauty standards have become narrowed to one point, namely Western-style beauty. This research aims to analyze how Skin Game, as a local beauty brand, contributes to changing the beauty narrative in Indonesia through the #BornThisWay campaign. This research uses a qualitative descriptive research type using Rholand Barthes' semiotics. The research subjects were 8 Skin Game Instagram posts with the hashtag BornThisWay. The reason for choosing the subject for the hashtag #BornThisWay is because posts with this hashtag are also a form of campaign carried out by Skin Game and have received a lot of positive responses from their followers as evidenced by the large number of Instagram users who have joined in using the hashtag. Then the object of research is the representation of beauty in Skin Game Instagram posts with the hashtag BornThisWay. In this research, researchers used the documentation method. According to Sugiyono in Gumelar (2020), the documentation method is a technique used to obtain data and information in the form of archives, books, writings or images or documents collected in a report for research purposes. Qualitative data analysis according to Bogdan and Biklen in Aldrian (2022) data analysis can be done through organizing data, sorting data so that it can be managed, synthesizing data, and continuing to search until it can produce something for other people from the research carried out. Through the results of this semiotic analysis, it can be interpreted that the #BornThisWay campaign by Skin Game succeeded in creating and communicating strong messages about self-acceptance, self-love, and celebrating individual physical uniqueness